Association between osteopontin expression and asthma: a meta-analysis. Issue 8 (August 2019) - Xu, Hangdi; Lou, Wei; Fu, Fangfang
Objective: Osteopontin (OPN) plays an important role in chronic airway remodeling and bronchial hyperresponsiveness. The association between OPN protein expression and asthma has been investigated extensively, but the results of these studies are inconsistent. The aim of this meta-analysis was to determine the relationship between OPN protein expression and asthma. Methods: A systematic search was performed to identify published studies regarding the association between OPN protein expression and asthma. Studies with quantitative data were analyzed, and standardized mean differences were determined with 95% confidence intervals. Results: Nine studies were included in this analysis, involving 706 patients with asthma and 332 healthy controls. The pooled data from these studies demonstrated that OPN protein expression was significantly higher in patients with asthma than in controls. There was no significant difference in OPN protein between allergic asthma and nonallergic asthma. Moreover, there was no obvious relationship between OPN protein expression and the severity of asthma. Conclusion: The results of this meta-analysis suggested that OPN protein expression is significantly upregulated in patients with asthma, but that it does not correlate with the type or severity of asthma.